Trends in Development Journalism in Student Publication: A Longitudinal Content Analysis - Laurence Lingat Ramos; Merwin Lad Velasco (Komunikologi: Jurnal Pengembangan Ilmu Komunikasi dan Sosial, 2026)
Student publications in Philippine higher education institutions play a significant role in development journalism, yet long-term trends in their development communication content remain understudied, particularly within agricultural and science-oriented state universities. This study analyzed the development communication content of the CLSU Collegian, the official student publication of Central Luzon State University, across periodical issues published from 2021 to 2025. Employing a mixed-methods design, the study combined descriptive quantitative analysis with qualitative framing and agenda-setting analysis of editorial and opinion articles. Findings revealed a consistent upward trend in development-related articles, growing from five in 2021 to nineteen in 2025. Education, Agriculture and Food Systems, and Economic Development emerged as the dominant thematic concerns throughout the period. Framing analysis showed a discernible shift from problem-focused to solution-oriented and advocacy-driven editorial perspectives, with issues consistently attributed to structural and institutional causes. Coverage scope also expanded from university-centered reporting toward local community and national development issues, reflecting the publication's growing agenda-building function. The study concludes that the CLSU Collegian has evolved into a meaningful platform for development journalism. It recommends institutionalizing the development communication section through editorial training and thematic planning, while encouraging future comparative research across similar public higher education institutions.